Respuesta :
The answer is b=-1 hopefully the s up so you can see my work and understand how I did it.
![Ver imagen alybsinger](https://us-static.z-dn.net/files/dd9/e31d854af20f9905f09928af7b43cdc7.png)
Answer:
b=-1
Step-by-step explanation:
[tex]5^{3b-1} = 5^{b-3}[/tex]
For any exponent, a^x
'a' is the base and x is the exponent
when the base are same on the both sides of equation then we equate the exponent
[tex]3b-1=b-3[/tex]
we solve for b
Subtract 'b' on both sides
[tex]2b -1= -3[/tex]
Add 1 on both sides
[tex]2b = -2[/tex]
Divide by 2 on both sides
b=-1